Development of Interactive Wordwall Media Using the PjBL (Project-Based Learning) Model in Science Subjects for 4th Grade Elementary School - Sofiyan Siregar Fatimah Siregar (International Conference on Education, Science, Technology and Health (ICONESTH), 2024)
This research is motivated by the use of IT available in schools that has not been used optimally by teachers. Inadequate development of innovative, interactive and fun media for students and the lack of development of technology-based learning media. Based on these problems, this study aims to develop learning media in the form of interactive wordwall media using the Project Based Learning (PjBL) model in science learning in grade IV elementary schools that is valid, practical and effective. This type of research is development research (R&D) using the ADDIE model. The ADDIE model consists of five steps, namely: analysis, design, development, implementation and evaluation. The designed media is then validated by the validator using a validation sheet in the form of a questionnaire. Product validation consists of material experts, media experts and language experts. For the practicality of the product, it is done by filling out the student's response questionnaire. The subjects of this study were divided into small group trials and field trials with 8 people each in the small group test and 20 people in the field trial. Keywords: Development, Student Learning Creativity, Project Based Learning, ADDIE.